The secret beyond matter - Yahya, Harun, 1956-; Okur Production (Istanbul : Okur Production, 2000)
This film discover how mistaken the materialist philosophy is, when it denies god by assuming that matter is absolute
Contents on videodisc: Warning; Introduction; How do we see?; the external world inside our brain; the world in dream; Who is the perceiver?; The real absolute being
This film based on the book 'Timelessness and the reality of fate'
Keywords: Man (Islam); Faith (Islam); Islamic cosmology